Does Organizational Justice Predict Empowerment? Nurses Assess Their Work Environment. Issue 5 (15th August 2014) - Kuokkanen, Liisa; Leino‐Kilpi, Helena; Katajisto, Jouko; Heponiemi, Tarja; Sinervo, Timo; Elovainio, Marko
Abstract Purpose The purpose of the study was to explore how nurses assess their empowerment and clarify organizational justice compared to other work‐related factors. In addition, we examined the major variables pertinent to empowerment. Design Cross‐sectional survey data were used. Methods A total of 2, 152 nurses returned the completed questionnaire. The instruments consisted of nurse empowerment, organizational justice, job control, and possibilities for developing work. The data analysis was based on descriptive statistics and further statistical tests. Findings Organizational justice and empowerment had a clear correlation. Job control, possibilities for developing work and organizational justice were statistically significant predictors of nurse empowerment. Conclusions Organizational justice and the possibility to use one's individual skills at work are significant factors in staff activity and its development in nursing. They increase the level of empowerment and commitment as well as motivation to work. Clinical Relevance The results of this study confirm that nurses regard organizational justice as highly important. We can facilitate both work‐related empowerment and organizational justice by creating and maintaining a culture of fairness and justice. Employees should be heard and involved more in the planning and decision making of work.